Bertolini (Shapiro), Ethel (audio interview #3 of 3) - Bertolini (Shapiro), Ethel ( - 2/2/1998); Bright, Susie, interviewer
INTERVIEW DESCRIPTION - This is the last of three interviews conducted with Ethel Bertolini as part of a project in a women's oral history class at CSULB. The interviewer was able to make connections and establish good rapport with the narrator as a result of her earlier participation in the University High School alternative newspaper, The Red Tide in the late 1960s/early 1970s. 11/00/1978